WVE‐005, a stereopure antisense oligonucleotide for MAPT silencing in tauopathies. (20th December 2022) - DaleMaguire, ElenaAbbie; Guo, Lankai; Byrne, Michael; Cannon, Megan; Taborn, Kris; Prakasha, Priyanka Shiva; Longo, Kenneth; Iwamoto, Naoki; Kandasamy, Pachamuthu; Shimizu, Mamoru; Shum, Pochi; Ranade, Ashwini; et al.
Abstract: Background : Tau is a neuronal scaffolding protein which aggregates intracellularly upon hyperphosphorylation to form neurofibrillary tangles (NFT). NFTs are a hallmark of various microtubule associated protein tau (MAPT)‐associated neurodegenerative diseases, including Alzheimer's disease, frontotemporal dementia, and progressive supranuclear palsy. Currently, there is no approved treatment targeting Tau pathology, nor any other disease‐modifying therapy for these diseases. Wave Life Sciences has developed a stereopure antisense oligonucleotide to reduce MAPT expression in patients with MAPT‐associated neurodegenerative diseases. Method : Using Wave's proprietary PRISM platform, we designed and screened stereopure oligonucleotides targeting MAPT in vitro and identified a lead sequence. PN chemistry was applied to the lead sequence in subsequent studies to further improve pharmacological properties. In vitro target engagement was measured in human iCell neurons after treatment with Wave's oligonucleotide, WVE‐005, or a published reference stereorandom oligonucleotide under gymnotic conditions. For in vivo analysis, transgenic mice received a single dose of 12.5, 25, 50, or 100µg oligonucleotide, and target engagement was measured after 4 weeks. To measure duration, transgenic mice received a single 100µg ICV dose and target engagement was tracked over 6 months. Finally, oligonucleotides were tested in non‐human primates (NHP) in a 12mg single‐dose intrathecal (IT) study. MAPT mRNA levels were quantified by qPCR, and intracellular distribution was evaluated by ViewRNA. Result : WVE‐005 showed dose‐dependent silencing of MAPT mRNA in iPSC‐derived neurons with an IC50 of 84nM. In a dose‐response study, 12.5µg and 25µg WVE‐005 led to 50% knockdown after 4 weeks in hippocampus and cortex, respectively, in transgenic mice. WVE‐005 led to >77% MAPT mRNA knockdown at 12 weeks post 100µg dosing, with knockdown of approximately 50% persisting 6 months post‐injection. In NHPs, WVE‐005 showed improved distribution and potency compared to non‐PN oligonucleotide with the same sequence. WVE‐005 decreased MAPT expression across NHP brain regions 28 days post‐single dose much greater than the non‐PN oligonucleotide and was detected in neuronal and glial cells. Conclusion : WVE‐005 potently and durably decreased MAPT mRNA expression in vitro and in multiple animal models, including throughout CNS upon IT administration in NHPs. These data support continued evaluation of WVE‐005 as a potential therapeutic for MAPT‐associated neurodegenerative diseases.